Analytical strategies for characterization of oxysterol lipidomes: Liver X receptor ligands in plasma - William Griffiths (Free Radical Biology and Medicine, 2012)
Bile acids, bile alcohols, and hormonal steroids represent the ultimate biologically active products of cholesterol metabolism in vertebrates. However, intermediates in their formation, including oxysterols and cholestenoic acids, also possess known, e.g., as ligands to nuclear and G-protein-coupled receptors, and unknown regulatory activities. The potential diversity of molecules originating from the cholesterol structure is very broad and their abundance in biological materials ranges over several orders of magnitude. Here we describe the application of enzyme-assisted derivatization for sterol analysis (EADSA) in combination with liquid chromatography-electrospray ionization-mass spectrometry to define the oxysterol and cholestenoic acid metabolomes of human plasma. Quantitative profiling of adult plasma using EADSA leads to the detection of over 30 metabolites derived from cholesterol, some of which are ligands to the nuclear receptors LXR, FXR, and pregnane X receptor or the G-protein-coupled receptor Epstein-Barr virus-induced gene 2. The potential of the EADSA technique in screening for inborn errors of cholesterol metabolism and biosynthesis is demonstrated by the unique plasma profile of patients suffering from cerebrotendinous xanthomatosis. The analytical methods described are easily adapted to the analysis of other biological fluids, including cerebrospinal fluid, and also tissues, e.g., brain, in which nuclear and G-protein-coupled receptors may have important regulatory roles